The Modification of PVDF Membrane via Crosslinking with Chitosan and Glutaraldehyde as the Crosslinking Agent - Romaya Sitha Silitonga; Nurul Widiastuti; Juhana Jaafar; Ahmad Fauzi Ismail; Muhammad Nidzhom Zainol Abidin; Ihsan Wan Azelee; Mahesan Naidu (Indonesian Journal of Chemistry, 2018)
Poly(vinylidene fluoride) (PVDF) has outstanding properties such as high thermal stability, resistance to acid solvents and good mechanical strength. Due to its properties, PVDF is widely used as a membrane matrix. However, PVDF membrane is hydrophobic properties, so as for specific applications, the surface of membrane needs to be modified to become hydrophilic. This research aims to modify PVDF membrane surface with chitosan and glutaraldehyde as a crosslinker agent. The FTIR spectra showed that the modified membrane has a peak at 1655 cm-1, indicating the imine group (–N=C)- that was formed due to the crosslink between amine group from chitosan and aldehyde group from glutaraldehyde. Results showed that the contact angle of the modified membrane decreases to 77.22° indicated that the membrane hydrophilic properties (< 90°) were enhanced. Prior to the modification, the contact angle of the PVDF membrane was 90.24°, which shows hydrophobic properties (> 90°). The results of porosity, Ɛ (%) for unmodified PVDF membrane was 55.39%, while the modified PVDF membrane has a porosity of 81.99%. Similarly, by modifying the PVDF membrane, pure water flux increased from 0.9867 L/m2h to 1.1253 L/m2h. The enhancement of porosity and pure water flux for the modified PVDF membrane was due to the improved surface hydrophilicity of PVDF membrane.